Asymmetric Synthesis of N‐Substituted α‐Amino Esters from α‐Ketoesters via Imine Reductase‐Catalyzed Reductive Amination. Issue 16 (9th March 2021) - Yao, Peiyuan; Marshall, James R.; Xu, Zefei; Lim, Jesmine; Charnock, Simon J.; Zhu, Dunming; Turner, Nicholas J.
Abstract: N ‐Substituted α‐amino esters are widely used as chiral intermediates in a range of pharmaceuticals. Here we report the enantioselective biocatalyic synthesis of N ‐substituted α‐amino esters through the direct reductive coupling of α‐ketoesters and amines employing sequence diverse metagenomic imine reductases (IREDs). Both enantiomers of N ‐substituted α‐amino esters were obtained with high conversion and excellent enantioselectivity under mild reaction conditions. In addition >20 different preparative scale transformations were performed highlighting the scalability of this system. Abstract : The asymmetric synthesis of N ‐substituted α‐amino esters has been achieved, in high yields and excellent enantioselectivities, employing sequence diverse metagenomic imine reductases (IREDs).